Analisis “Kegagalan” Pendaftaran Tanah Sistematis Lengkap di Kabupaten Pati - Parenta, Thezar Prymori (Sekolah Tinggi Pertanahan Nasional, 2022)
Cluster 3 is a product of the Complete Systematic Land Registration/ Pendaftaran Tanah Sistematis Lengkap (PTSL) where physical data collection has been carried out on PTSL objects, but the certificate cannot be issued due to several reasons behind it. Cluster 3 in the implementation of PTSL in Pati Regency is 83,873 fields, this number is an accumulation of cluster 3 within a period of three years, namely from 2019 to 2021 and there has been no significant effort made by the Pati Regency Land Office to suppress or solve the cluster 3 problem. The method used in this study is a qualitative method with observation and interview. The results of research that has been carried out in two villages in Pati Regency, namely Prawoto Village and Wegil Village show that the factors causing cluster 3 in the implementation of PTSL are unproductive soil conditions, the delivery of information on the implementation of PTSL that is not on target to the community, there is a concern for the community towards the land program. Another thing is that the ease of access to capital (without land certificates) in banks contributes to the refusal of people to be involved in PTSL. The author concludes that the state should take more appropriate approaches regarding the needs and guarantees of legal certainty over residents' land, because the legalization of assets in addition to the state's need to map all land is also to be able to guarantee the certainty of land owned by the community.